PELAKSANAAN PENDAFTARAN TANAH WAKAF TERHADAP TANAH YANG BELUM BERSERTIPIKAT DI KECAMATAN BUKIT RAYA - Hazra, Filza Amalia; Haryono, Dodi; Bachtiar, Maryati (Jurnal Ekonomi Bisnis Kompetif, 2025)
Waqf land must have a clear legal status through the waqf land certification process to avoid potential disputes. In fact, in Bukit Raya District, there are still many waqf lands that have not been certified. The objectives of this study are first, how is the implementation of waqf land registration for uncertified land in Bukit Raya District. Second, what are the obstacles in registering waqf land for uncertified land in Bukit Raya District. Third, how are the efforts to overcome obstacles in registering waqf land for uncertified land. This type of research is classified as a sociological research type. This study uses data sources in the form of primary data and secondary data, and data collection techniques are carried out by interviews and literature reviews. The results of this study indicate that the Implementation of Waqf Land Registration for Uncertified Land in Bukit Raya District has been in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 2 of 2017, Obstacles in registering waqf land for uncertified land are the lack of public understanding and limited resources at the KUA Bukit Raya District and the Pekanbaru City Land Office. Efforts to overcome obstacles in registering waqf land are to increase socialization to the community, appoint a PIC, and improve the quality of resources at the KUA Bukit Raya District and the Pekanbaru City Land Office. Keywords: Wakaf, Pendaftaran Tanah Wakaf, dan Sertipikat Wakaf